2009
DOI: 10.2528/pier09020801
|View full text |Cite
|
Sign up to set email alerts
|

On the Application of Microwave Calibration-Independent Measurements for Noninvasive Thickness Evaluation of Medium- Or Low-Loss Solid Materials

Abstract: Abstract-Microwave methods require some sort of calibration before physical (thickness, flaw, etc.) and electrical (permittivity, permeability, etc.) measurements of materials. It is always attractive to devise a method which not only eliminates this necessity but also saves time before measurements. Microwave calibration-independent measurements can be utilized for this goal. However, in the literature, these measurements are only applied for electrical measurements of materials. In this research paper, we in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…First, the accuracy of physical measurements increases for thicker samples. Second, the ability of any measurement instrument to resolve or detect measurements at sequentially and linearly separated frequencies for thicker samples is greater than for thinner samples [33]. In addition, we observed that the accuracy of thickness evaluation for Plexiglas slabs is better than that of PTFE slabs.…”
Section: Measurement Resultsmentioning
confidence: 78%
See 2 more Smart Citations
“…First, the accuracy of physical measurements increases for thicker samples. Second, the ability of any measurement instrument to resolve or detect measurements at sequentially and linearly separated frequencies for thicker samples is greater than for thinner samples [33]. In addition, we observed that the accuracy of thickness evaluation for Plexiglas slabs is better than that of PTFE slabs.…”
Section: Measurement Resultsmentioning
confidence: 78%
“…The microwave methods generally applied to materials testing and evaluation are free-space [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24], waveguide transmission line [25][26][27][28][29][30][31][32][33], and open-ended waveguide coaxial methods [34][35][36][37][38][39][40][41][42][43]. While open-ended waveguide or coaxial (or parallel plate) methods are very sensitive to materials' (and composite structures') properties (thickness, disbonding, delamination, and etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dielectric constant is equivalent to relative permittivity (ε r ), or the absolute permittivity (ε) is relative to the permittivity of free space (ε 0 ) [56][57][58][59][60][61][62][63][64][65]. The dielectric constant of a material also affects the velocity of microwave signals when it moves through the material.…”
Section: Defining the Dielectric Propertiesmentioning
confidence: 99%
“…Microwave measurements are preferred in various applications such as defining material properties [1], microwave radars [2], measurement of the frequency response of RF and millimeter wave circuits and components, and characterizing radio channels [3]. This is due to the good penetration properties of microwaves.…”
Section: Introductionmentioning
confidence: 99%